Immuno-inflammatory pathogenesis in ischemic heart disease: perception and knowledge for neutrophil recruitment - Wang, Yumeng; Shou, Xintian; Wu, Yang; Li, Dong (Frontiers in Immunology, 2024)
Ischemic heart disease (IHD) can trigger responses from the innate immune system, provoke aseptic inflammatory processes, and result in the recruitment and accumulation of neutrophils. Excessive recruitment of neutrophils is a potential driver of persistent cardiac inflammation. Once recruited, neutrophils are capable of secreting a plethora of inflammatory and chemotactic agents that intensify the inflammatory cascade. Additionally, neutrophils may obstruct microvasculature within the inflamed region, further augmenting myocardial injury in the context of IHD. Immune-related molecules mediate the recruitment process of neutrophils, such as immune receptors and ligands, immune active molecules, and immunocytes. Non-immune-related molecular pathways represented by pro-resolving lipid mediators are also involved in the regulation of NR. Finally, we discuss novel regulating strategies, including targeted intervention, agents, and phytochemical strategies. This review describes in as much detail as possible the upstream molecular mechanism and external intervention strategies for regulating NR, which represents a promising therapeutic avenue for IHD.